PENGARUH KUALITAS PELAYANAN SURAT IZIN GANGGUAN TERHADAP KEPUASAN PUBLIK PADA BADAN PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN MAMUJU UTARA - Rusman, Rusman (Katalogis, 2016)
The purpose of this study were (1) to analyze the simultaneous effect of variables of service quality permit disruption of public satisfaction with the Board of Investment and Integrated Services One Stop Mamuju Utara, (2) analyze the effect of the partial service quality variables permit disruption of public satisfaction on Investment Board Capital and Integrated Services One Stop North Mamuju regency. The main theory used is Parasuraman The amount of sample of 33 people. Model analysis used is multiple linear regression. Results of the study (1) Quality of Service Permit Disorders simultaneously significant effect to the satisfaction of the Public Investment Board and One Stop Mamuju Utara (2) Quality of Service License Disorders partially significant effect to the satisfaction of the Public Investment Board and Services One Stop Mamuju Utara.Dari physical evidence diperolehVariabel research results become the biggest factor affecting public satisfaction mainly due to the comfort of the workplace availability waiting room equipped with a fan and a television so that people feel comfortable while waiting for the permit, then the variable certainty, especially knowledge apparatus due to officials who handle permits have followed training and responsible and trustworthy, then the variable reliability especially fast service due to personnel who have experience in the service permits, then the variable responsiveness, especially the provision of information caused by the authorities in providing information clear and easy to understand by society, then the lowest factor affecting public satisfaction is variable empathy with the ability to master the forces caused by the apparatus information about licensing issues.Â symbol indicates confounding variables that affect public satisfaction but are not included in this study.